Conceptualization of a Collaborative Decision Making for Flood Disaster Management - Zubir S.N.A.; Thiruchelvam S.; Mustapha K.N.; Muda Z.C.; Ghazali A.; Hakimie H.; Abdul Razak N.N.; Mat Isa A.A.; Hasini H.; Mohamed Sahari K.S.; Husin N.M.; Rusli M.E.; et al. (Institute of Physics Publishing, 2023)
Behavioral research; Disaster prevention; Disasters; Floods; Human resource management; Collaborative decision making; Flood disaster management; Flood duration; Government agencies; Integral element; Natural hazard; Sharing resources; Social-economic; Decision making; conceptual framework; coping strategy; decision making; disaster management; environmental response; flood damage; flooding; intergovernmental relations; natural hazard; Malaysia; West Malaysia